(untitled) (Globalization and Business, 2018)
Public Debt sustainability is an important factor of indicators of debt sustainability are below the thresholds. Nevertheless, a shock tests indicate that debt sustainability is vulnerable to permanent long term and to sharp short term shocks. In order to maintain low risk for debt sustainability, the study shows that the GDP growth rate in Georgia in the medium term should be at least 7% and the budget deficit should be below 3% of GDP for the same time period.macroeconomic sustainability of Georgia. The decrease of economic growth rates in Georgia and increased fiscal deficit and public debt (both, foreign and internal) since 2008 year have made it actual to assess the debt sustainability of the country both, in medium term and long term perspectives.The analysis evidenced that by the 2018 most marginal indicators of debt sustainability are below the thresholds. Nevertheless, a shock tests indicate that debt sustainability is vulnerable to permanent long term and to sharp short term shocks. In order to maintain low risk for debt sustainability, the study shows that the GDP growth rate in Georgia in the medium term should be at least 7% and the budget deficitshould be below 3% of GDP for the same time period.